Progress in Computational Physics (PiCP) Vol : 2 Coupled Fluid Flow in Energy, Biology and Environmental Research. - Ehrhardt, Matthias (Progress in Computational Physics (PiCP), 2012)
This second volume contains both, the mathematical analysis of the coupling between fluid flow and porous media flow and state-of-the art numerical techniques, like tailor-made finite element and finite volume methods. Readers will come across articles devoted to concrete applications of these models in the field of energy, biology and environmental research.